2007
DOI: 10.1111/j.1748-1716.2007.01673.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of expression of Na+/Ca2+ exchanger in heart of rat and mouse under stress

Abstract: The gene expression and protein levels of the NCX1 are increased by the strong stress stimuli, e.g. hypoxia, or immobilization stress. The activity of NCX1 is decreased. Based on these results, we assume that the gene expression of NCX is increased as a consequence of suppressed activity of this transport system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Wash-out of DMOG for 3 hours did not result in a reduction of the NCX1 mRNA and protein to original, control levels, although pH returned to control values. Our results are in agreement with our previous studies (Hudecova et al 2007), where we observed significant increase in NCX1 mRNA and protein in hypoxic cardiomyocytes. Moreover, upregulation of the NCX1 expression and activity observed in microglia after permanent middle cerebral artery occlusion suggests a relevant role of NCX1 in modulating microglia functions in the postischemic brain (Boscia et al 2009).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Wash-out of DMOG for 3 hours did not result in a reduction of the NCX1 mRNA and protein to original, control levels, although pH returned to control values. Our results are in agreement with our previous studies (Hudecova et al 2007), where we observed significant increase in NCX1 mRNA and protein in hypoxic cardiomyocytes. Moreover, upregulation of the NCX1 expression and activity observed in microglia after permanent middle cerebral artery occlusion suggests a relevant role of NCX1 in modulating microglia functions in the postischemic brain (Boscia et al 2009).…”
Section: Discussionsupporting
confidence: 94%
“…In our previous studies we have shown that short-term hypoxia (8% oxygen for 6 hours) significantly increased gene expression and protein levels of the NCX1 in rat cardiomyocytes (Hudecova et al 2007). Hypoxia is a state of insufficient oxygen supply of the tissue or cell.…”
Section: Introductionmentioning
confidence: 96%
“…However, sustained stress also inhibits NCX1 activity, an effect that requires corticosteroid release in concert with adrenergic activation. 36 Reversible protein phosphorylation is essential for excitation-contraction coupling, Ca 2+ handling, cell metabolism, myofilament regulation, and cell-cell communication. 37 ~90% of dephosphorylation events are catalysed by just three phosphatases: PP1, PP2A and PP2B (calcineurin), all of which are regulated by microRNA we identified as changing after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia activates the L-type calcium channels in pulmonary vasculature (Weir and Olschewski 2006). Also, hypoxia significantly increases gene expression and also protein levels of the sodium-calcium exchanger type 1 (NCX1) in the rat cardiomyocytes (Hudecova et al 2007) and in human embryonic kidney (HEK 293) cell line (Hudecova et al 2011), probably through the HIF-1α. NCX1 plays a key role in inducing apoptosis after hypoxia in cultured guinea pig ventricular myocytes (Eigel et al 2004).…”
Section: Ip 3 Receptors and Stressmentioning
confidence: 99%